2018
DOI: 10.1111/dom.13549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium supplementation on changes in HbA1c: Results from a multiple‐dose, randomized controlled trial

Abstract: Aim To investigate the effect of selenium supplementation at different dose levels on changes in HbA1c after 6 months and 2 years in a population of low selenium status. Materials and Methods The Denmark PRECISE study was a single‐centre, randomized, double‐blinded, placebo‐controlled, multi‐arm, parallel clinical trial with four groups. In total, 491 volunteers aged 60 to 74 years were randomly assigned to treatment with 100, 200 or 300 μg selenium/day as selenium‐enriched yeast or placebo‐yeast. HbA1c measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
(148 reference statements)
1
17
0
Order By: Relevance
“…Two RCTs on selenium supplementation carried out in Danish elderly and Polish adults reinforce our main result that higher intakes of selenium are associated with lower concentrations of HbA 1c , even within different populations and with different doses of selenium ( 16 , 38 ). By contrast, some studies have failed to demonstrate a decrease in HbA 1c concentrations ( 12 , 39 ) or found high serum selenium concentrations associated with increased concentrations of glucose and HbA 1c , as in 41,474 American adults with a mean dietary selenium intake of 98.0 ± 55.0 μg/day ( 40 ) and in 8,824 Chinese with a mean consumption of 52.4 μg/day ( 41 ).…”
Section: Discussionsupporting
confidence: 66%
“…Two RCTs on selenium supplementation carried out in Danish elderly and Polish adults reinforce our main result that higher intakes of selenium are associated with lower concentrations of HbA 1c , even within different populations and with different doses of selenium ( 16 , 38 ). By contrast, some studies have failed to demonstrate a decrease in HbA 1c concentrations ( 12 , 39 ) or found high serum selenium concentrations associated with increased concentrations of glucose and HbA 1c , as in 41,474 American adults with a mean dietary selenium intake of 98.0 ± 55.0 μg/day ( 40 ) and in 8,824 Chinese with a mean consumption of 52.4 μg/day ( 41 ).…”
Section: Discussionsupporting
confidence: 66%
“…Therefore, long term supplementation needs special attention and it might be recommended to monitor glycemia after a few weeks. However, recent studies have been reassuring regarding dosages < 300 mcg notably for type 2 diabetes and prostate cancer (121)(122)(123)(124)(125). Long term 200 mcg Selenium supplementation in randomized controlled trials in HIV infection has been shown to be well-tolerated (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, plasma samples (50 µL) were diluted 1:100 in a diluent containing; Triton-X-100 (0.05%), ammonium hydroxide (NH 4 OH) (1%), ethylenediaminetetraacetic Acid (EDTA; 0.05%), and Butanol (2%) (Sigma-Aldrich, Taufkirchen, Germany). Butanol was added to compensate for differences in carbon content between the samples and standards that may cause variances in ionization efficiency leading to erroneous results [ 63 , 64 ]. Rhodium (Rh) was used as an internal standard for accuracy to correct for any instrumental drift.…”
Section: Methodsmentioning
confidence: 99%